STUDY OF THE EFFECT OF THE TIDES ON THE KARANG MUMUS RIVER (TRIBUTARY OF THE MAHAKAM) ON THE DRAINAGE SYSTEM IN THE CITY OF SAMARINDA - Triyatno, Gading
Floods in Samarinda City are events that occur regularly (latent) with increasing inundation area and deep water level. factors that cause flooding such as changes in channel dimensions, accumulation of sedimentation and tidal influences from the Karang Mumus River. This study discusses the flood management strategy that occurred in the city of Samarinda which is included in the watershed area of the Karang Mumus River downstream which is divided into several zones, Zone I, Zone II, Zone III, Zone IV, Zone V, Zone VI dan Zone VII, carry out canal rehabilitation, rehabilitate canals due to the influence of drainage modulus and tidal conditions on the existing condition and the design condition. Based on analysis results of the 203 drainage channels, there are 155 drainage channels that have a capacity less than the design discharge. For channels located in the downstream drainage network system, before the water flows into the Karang Mumus River, channels in the zones are given freeboard so that it can accommodate the load of the drainage modulus so that it does not overflow, for Zone I = 0,9 m, Zone II = 0,8 m, Zone III = 0,9 m, Zone IV = 0,8 m, Zone V = 0,9 m, Zone VI = 0,7 m dan Zone VII = 0,8 m. Apart from the influence of the load on the drainage modulus, these channels are also affected by tidal water from the Karang Mumus River. The tidal type in the Karang Mumus River is Mixed Semi – Diurnal with Formzhal number = 0,4, based on hydro-topographic classification the area of the Karang Mumus River downstream is included in Category C. So that the channel can accommodate water in these conditions, it is made square with width 3,5 – 23,5 m, channel height 1,3 – 2,5 m, with capacity 32.300 m3 in Zone I, 7.350 m3 in Zone II, 16.500 m3 in Zone III, 63.000 m3 in Zone IV, 8.648 m3 in Zone V, 22.239 m3 in Zone VI, 21.192 m3 in Zone VII.